2017
DOI: 10.3390/app7060501
|View full text |Cite
|
Sign up to set email alerts
|

Separation Control on a Bridge Box Girder Using a Bypass Passive Jet Flow

Abstract: Abstract:In the present study, a bypass passive jet flow control method was proposed to mitigate unsteady wind loads and to manipulate the flow field around a single box girder of a bridge. With a geometric ratio of 1:125, the single box girder model was determined using the cross-section of the Great Belt East Bridge. During the experiments, one test model without control was adopted, while five different test models with different suction/jet configurations were employed to analyze the effects of the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
1
3
0
2
Order By: Relevance
“…Therefore, the box girder of the bridge is designed as near streamline for alleviating the VIV. Due to the box girder being not entirely streamlined, the VIV often happens when the airflow velocity attains a specific value, i.e., the wake vortex frequency is equal to that of the box girder at this velocity [2,9]. In addition, the affiliate parts (i.e., railing, maintenance track, and streetlamps) that are set in the box girder also can affect the characteristics of the main girder and the fluctuation of the aerodynamic force.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the box girder of the bridge is designed as near streamline for alleviating the VIV. Due to the box girder being not entirely streamlined, the VIV often happens when the airflow velocity attains a specific value, i.e., the wake vortex frequency is equal to that of the box girder at this velocity [2,9]. In addition, the affiliate parts (i.e., railing, maintenance track, and streetlamps) that are set in the box girder also can affect the characteristics of the main girder and the fluctuation of the aerodynamic force.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that a sudden change in wind speed near the bridge pylon is unfavorable for driving stability [18], and countermeasures have been explored for improving the wind environment at the bridge deck and ensuring driving safety [19,20]. Wind barriers, as an effective countermeasure, have had increasing attention from scholars [21][22][23]. Alonso-Estebanez et al [24] numerically studied and compared the aerodynamic coefficients of a truck on an embankment both with and without the wind fences installed.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang ve arkadaşları [7] tabliyenin alt yüzeylerine açtıkları deliklerden akış emme işlemi gerçekleştirilmesinin tabliye art izindeki girdapları bastırdığını ve bunun sonucu olarak salınımların azaltıldığını ve sürüklenme katsayısının kontrol yöntemi uygulanmadığı durum ile kıyaslandığında %75 oranında azaldığını yaptıkları sayısal çalışma ile göstermişledir. Zhang ve arkadaşları [8] Bu çalışmada, ikiz tabliyeler arasındaki akışın, iki tabliye arasına yerleştirilen ve tabliyelere paralel uzanan dairesel kesitli çubuk ile kontrolü hedeflenmiştir. Tabliyeler arasındaki mesafenin tabliye yüksekliğine oranı L/H=1,7 ve dairesel kesitli çubuk çapının tabliye yüksekliğine oranı D/H=0,11 seçilmiştir.…”
Section: Introductionunclassified
“…Zhang ve arkadaşları [7] tabliyenin alt yüzeylerine açtıkları deliklerden akış emme işlemi gerçekleştirilmesinin tabliye art izindeki girdapları bastırdığını ve bunun sonucu olarak salınımların azaltıldığını ve sürüklenme katsayısının kontrol yöntemi uygulanmadığı durum ile kıyaslandığında %75 oranında azaldığını yaptıkları sayısal çalışma ile göstermişledir. Zhang ve arkadaşları [8] [15] tabliyeler arasındaki mesafenin tabliye yüksekliğine oranının, L/H=1.7 değerinde yaptıkları deneysel çalışma ile tabliyelerin belirli aralıkla birbirlerine kiriş ve çapraz çubuklar ile bağlandığında girdap kaynaklı titreşimlerin tamamen bastırıldığını göstermişlerdir. Ma ve arkadaşları [16] tabliyeler arasına yerleştirdikleri gözenekli plakların akış kontrolü üzerine etkisini deneysel çalışma ile araştırmışlardır.…”
Section: Introductionunclassified